Coronavirus in News Text: Critical Discourse Analysis Detik.Com News Portal - Ida Ismiyati; Rida Nurlatifasari; Sumarlam Sumarlam (Journal of English Language Teaching and Linguistics, 2021)
At this time the whole world is being attacked by a virus called the Corona Virus or Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) is a type of virus that attacks the human respiratory system. This disease due to viral infection is called COVID-19. COVID-19 is a polemic that causes concern for the community due to its rapid spread and even causes many deaths, including in Indonesia. The condition of this social situation makes a lot of news done, one of which is related to prevention with social distancing published by Detikcom. This study aims to conduct a critical analysis of articles about COVID-19 on Detikcom. This research uses a descriptive method. The object of the research is an article entitled "Tentang Social Distance, Cara Pemerintah Cegah Penyebaran Virus Corona" released on Monday, March 16, 2020, by Detikcom. Data analysis was performed using Fairclough's critical discourse analysis. The results show that the text in the discourse has been selected using the appropriate words to represent the expectations of a social distancing policy and is also able to represent the social conditions of the panicked community with the outbreak of COVID-19. The discourse in the text has also been able to provide feedback in the form of the social conditions of the community which can be a little calm with the existence of the policies that have been released as well as the direct role of the government and the credibility of Detikcom. The ideology is related to influencing society in implementing social distancing for the success of Government programs. Thus, this research will foster public confidence in dealing with this coronavirus and influence to implement social distancing during the COVID-19 pandemic.